Effects of long-term metformin intake on postoperative clinicopathological characteristics in patients with invasive lung adenocarcinoma and type 2 diabetes mellitus: A retrospective analysis. - Xiaowen Zhang; Jingwei Liu; Ziwei Zhao; Jie Jiang; Guojun Geng (PLoS ONE, 2025)
Objective This retrospective study aimed to evaluate whether long-term metformin use is associated with less aggressive clinicopathological characteristics in patients with invasive lung adenocarcinoma (LUAD) and type 2 diabetes mellitus (T2DM). Methods We reviewed patients with both invasive LUAD and T2DM who underwent curative lung cancer resection and lymph node dissection between January 2012 and August 2022. Patients were divided into a metformin group and a non-metformin group based on their antidiabetic treatment. Clinicopathological outcomes included tumor size, TNM stage, histologic differentiation, Ki-67 expression, and pathological subtypes. Comparisons were made using Student's t-test, Mann-Whitney U test, χ² test, or Fisher's exact test, as appropriate. Results A total of 130 patients were included (45 metformin users and 85 non-users), with no significant differences in baseline characteristics. The metformin group showed smaller tumors (1.78 ± 0.87 cm vs. 2.21 ± 1.28 cm; p = 0.049), fewer cases of high Ki-67 expression (>15%) (35.6% vs. 62.3%; p = 0.004), and no lymph node metastasis (0% vs. 15.3%; p = 0.022). Additionally, patients on metformin had better differentiation (p = 0.039) and earlier TNM stages (p = 0.03). Conclusion Long-term metformin use in diabetic patients with invasive LUAD was associated with more favorable clinicopathological features, including smaller tumor size, lower proliferative index, and absence of nodal metastasis. These findings support a potential anti-tumor role of metformin in lung adenocarcinoma.